2017
DOI: 10.22225/jr.1.1.16.108-122
|View full text |Cite
|
Sign up to set email alerts
|

Konstruksi Pasif Bahasa Manggarai: Sebuah Analisis Leksikal – Fungsional

Abstract: Data dalam artikel ini merupakan hasil penelitian lapangan dengan menggunakan suatu metode pengamatan, wawancara secara mendalam, dan intuitif. Dari hasil analisis data diperoleh gambaran bahwa konstruksi pasif yang ditemukan dalam bahasa Manggarai adalah konstruksi pasif sintaktis, yang terdiri atas pasif kanonis dan pasif nonkanonis. Pasif morfologis tidak terdapat pada bahasa ini. Hal ini beralasan karena bahasa Manggarai tidak memiliki pemarkah morfologis, terutama afiksasi. Argumen inti satu-satunya dalam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The argument structure is an intermediate structure in which information is contained, namely (a) information about the valence of verbs (such as verbs with one argument, verbs with two arguments, and verbs with three arguments); (b) information about the essence of the argument (core argument and non-core argument); (c) information about the prominence of an argument that has (i) core over non-core, and (ii) in this series of core and non-core prominence describes semantic prominence (Arka, 1998(Arka, , 2003a(Arka, , 2003bManing, 1996;Alsina, 1996in Kosmas, 2008.…”
Section: Theoritical Reviewmentioning
confidence: 99%
“…The argument structure is an intermediate structure in which information is contained, namely (a) information about the valence of verbs (such as verbs with one argument, verbs with two arguments, and verbs with three arguments); (b) information about the essence of the argument (core argument and non-core argument); (c) information about the prominence of an argument that has (i) core over non-core, and (ii) in this series of core and non-core prominence describes semantic prominence (Arka, 1998(Arka, , 2003a(Arka, , 2003bManing, 1996;Alsina, 1996in Kosmas, 2008.…”
Section: Theoritical Reviewmentioning
confidence: 99%
“…(Cholisi, 2013) added that the Indonesian verb structure always related to adjunct and oblique objects. Then, (Kosmas, 2015) used this Lexical Functional Grammar (LFG) Theory, especially in constituent structure and functional structure, to analyze the passive construction in the Manggarai language. And as a result, (Kosmas, 2015) found that the Manggarai language is passive syntactic construction because this language does not have a phonological marker.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Then, (Kosmas, 2015) used this Lexical Functional Grammar (LFG) Theory, especially in constituent structure and functional structure, to analyze the passive construction in the Manggarai language. And as a result, (Kosmas, 2015) found that the Manggarai language is passive syntactic construction because this language does not have a phonological marker. (Romadhan, 2019) also did X-Comp analysis in the Indonesian language using Lexical Functional Grammar, and there was destruction of arguments in the embedded verbs in X-Comp.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Manggarai ethnic group develops a linguistic system and culture that is typically unique and diverse from other communities settling in the western part of Flores Island, Indonesia. Linguistically, Manggarai language is the Austronesian language of Nusantara, categorised as the isolating language; it lacks morphological affixation and pronominal agreement on the verb (Arka, 2002;Jeladu, 2020). Moreover, it has distinctive phonetic and phonotactic features in the case of phoneme combination and pre-phoneme nasal sounds (Karjo, 2022).…”
Section: Introductionmentioning
confidence: 99%